Documentary Photography and the Representation of Life on the Streets in Two Works by Martha Rosler and Jeff Wall: Ethical and Aesthetic Considerations - Gwen Cressman (IdeAs)
Four decades separate Martha Rosler’s The Bowery in two inadequate descriptive systems (1974-1975) from Jeff Wall’s Approach (2014), two representations of life on the streets. In the 1970s, Martha Rosler, among others, sought to define and practice documentary photography in ways that would invite the viewer to reflect on the politics of representation at work in documentary art. Forty years later, in his work Approach, representing a homeless woman, Jeff Wall, in the style he describes as “near-documentary”, also questions notions of objectivity, authenticity and realism in photography. The balance that both Wall and Rosler pursue between proximity with reality taken as lived experience and distance from the illusion of the authentic moment is emblematic of a shared strategy. Through the dialectic of visibility and invisibility, this strategy aims at revealing the double process at work in documentary photography, that of approaching a subject and establishing a distance with it. The radical act of “not photographing” ironically present in both works underlines the ways in which Rosler and Wall are engaged in a critique of the politics of visibility.